Estudio de mejora a una fábrica de aceite y cáscara deshidratada de limón realizada por Corporación Primax para el cambio de matriz energética de petróleo diesel y residual a gas licuado de petróleo - Sánchez Torino, Aníbal Guillermo (2020)
This work presents the Improvement Study to switch the energy source of a factory producing lime oil and dried lime peel in Northern Peru. The design of the LPG system considered the technical characteristics and requirements for the consumption equipment and its distance towards the storage area in accordance with Peruvian Technical Standards NTP 321.123 and NTP 321.121 (NTP, for its Spanish acronym), and other international standards including NFPA 58, CE and ASME. This study confirmed that the client’s plant layout in the lime oil production line could be optimized by relocating the steam boilers to a different area. The storage system ensures a fuel stock that allows for autonomy to respond to any shortages due to an undersupply of LPG or strikes that may interrupt access to LPG units. The forced vaporization system was designed to ensure a constant pressure and flow during periods of high consumption. The piping networks and LPG accessories were designed to avoid load losses or pressure drops during the production operation. It was recommended that high speed burners for drying furnaces and Monoblock burners for steam boilers be installed. The power of the burners for rotary furnaces was calculated through a matter and energy balance considering the amount of the product to be dried, the entry and exit humidity, the drying time, the heat losses through furnace walls and the losses in the air flow. Emissions and maintenance service costs were reduced by replacing residual oil burners with LPG burners. Furthermore, additional automation accessories were installed (humidity controls, modulating temperature controls, among others), thus optimizing the production processes. The duration of the project is five years, and its economic profitability indicators were determined in the study. Moreover, the contract with the client stated that if the fuel consumption in this period of time was reached earlier, the contract would then expire. Otherwise, the contract would be extended until consumption was reached. The annual savings resulting from switching from oil to LPG allowed the client to achieve a higher profit margin for the sale of its products.